THE PLACE OF MUSIC IN EDUCATION OF YOUNG PEOPLE (Multidisciplinary Journal of Science and Technology, 2025)
In this article, the role and importance of music in the education of young people is fully explained. The meanings of words and sounds in music are also mentioned. At the moment, the government is paying a lot of attention to the education and upbringing of young people on the scale of the republic. The main goal of many pedagogic researchers is to increase the rate of acceptance of education and training by students, and this article presents a theoretical and comparative analysis of the role of national music in the development and education of young people.